2009
DOI: 10.1016/j.neuroimage.2009.01.058
|View full text |Cite
|
Sign up to set email alerts
|

The role of the nucleus accumbens and rostral anterior cingulate cortex in anhedonia: Integration of resting EEG, fMRI, and volumetric techniques

Abstract: Anhedonia, the reduced propensity to experience pleasure, is a promising endophenotype and vulnerability factor for several psychiatric disorders, including depression and schizophrenia. In the present study, we used resting electroencephalograms, functional magnetic resonance imaging, and volumetric analyses to probe putative associations between anhedonia and individual differences in key nodes of the brain's reward system in a non-clinical sample. We found that anhedonia, but not other symptoms of depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
243
7
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 358 publications
(273 citation statements)
references
References 104 publications
(173 reference statements)
21
243
7
2
Order By: Relevance
“…Furthermore, rBN subjects were unable to distinguish between negative and positive feedback in the dorsal caudate nucleus, a region implicated in linking action to outcome (Wagner et al, 2010). Critically, response bias as measured by the current task has been found to correlate with reward-related activation in striatal regions Wacker et al, 2009) and was modulated by dopaminergic challenges (Pizzagalli et al, 2008). Together with these prior findings, the current data highlight an impaired, dopaminergic-mediated tendency to modulate behavior as a function of prior reinforcements in individuals with a history of BN.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, rBN subjects were unable to distinguish between negative and positive feedback in the dorsal caudate nucleus, a region implicated in linking action to outcome (Wagner et al, 2010). Critically, response bias as measured by the current task has been found to correlate with reward-related activation in striatal regions Wacker et al, 2009) and was modulated by dopaminergic challenges (Pizzagalli et al, 2008). Together with these prior findings, the current data highlight an impaired, dopaminergic-mediated tendency to modulate behavior as a function of prior reinforcements in individuals with a history of BN.…”
Section: Discussionmentioning
confidence: 63%
“…Recent research on the neurobiology of major depression has also focused on the ACC. More specifically, the major depression symptom of anhedonia, characterized by reward-insensitive behavior and blunted positive emotionality -and hence, apparently, the extremely low end of aE (Depue, 1995) -has been associated with abnormally low levels of activity in the ventral-rostral ACC (rACC) regions (Pizzagalli, Peccoralo, Davidson, & Cohen, 2006) and with blunted nucleus accumbens responses to reward signals (Wacker, Dillon, & Pizzagalli, 2009). Furthermore, pharmacological challenge studies have demonstrated that the ACC responds to dopaminergic drugs (e.g., Völlm et al, 2004), and ACC activity also qualifies as a predictor for psychopharmacological treatment responses (for selective norepinephrine and serotonin reuptake inhibitors, see Korb, Hunter, Cook, & Leuchter, 2009).…”
Section: Agentic Extraversion and Anterior Cingulate Cortex Activitymentioning
confidence: 99%
“…The second aim was to investigate the relationship between reward processing and nucleus accumbens volume in PCP and controls. Since anhedonia is common in PCP and interacts with both reward responsiveness (Beevers and Meyer, 2002) and nucleus accumbens volume (Harvey et al, 2007;Wacker et al, 2010), correlation analyses were corrected for anhedonia.…”
Section: Introductionmentioning
confidence: 99%